From experience to action in recovery-oriented mental health practice: A first person inquiry. Issue 4 (December 2014) - Kidd, Susan; Kenny, Amanda; McKinstry, Carol
This article reports on the development of critical subjectivity, in a cooperative inquiry study, which aimed to use principles of consumer participation to explore and develop recovery-oriented care in a regional mental health service in rural Australia. The development of critical subjectivity occurred when the lead researcher began to understand her role as an 'insider' in perpetuating dominant institutional culture through her work practices. The findings illustrate the way lived experience perspectives were excluded, invisible and considered 'outsider' in relation to dominant biomedical epistemology. As the researcher participated in a more relational participatory process and documented her thinking, her knowledge of her work practices began to change and this contributed to the transformation in her practice. Action research is a tool that supports shared dialogue to enable culture change necessary for recovery-oriented practice.